Dietary patterns and associated lifestyles in individuals with and without familial history of obesity: a cross-sectional study - Vohl Marie-Claude; Pérusse Louis; Paradis Ann-Marie (BMC, 2006)
Abstract Background Familial history of obesity (FHO) and certain dietary habits are risk factors for obesity. The objectives of this cross-sectional study were 1) to derive dietary patterns using factor analysis in a population of men and women with and without FHO; 2) to compare mean factor scores for each dietary pattern between individuals with and without FHO; and 3) to examine the association between these patterns and anthropometric, lifestyle and sociodemographic variables. Methods A total of 197 women and 129 men with a body mass index <30 kg/m2 were recruited. A positive FHO (FHO+) was defined as having at least one obese first-degree relative and a negative FHO (FHO-) as no obese first-degree relative. Dietary data were collected from a food frequency questionnaire. Factor analysis was performed to derive dietary patterns. Mean factor scores were compared using general linear model among men and women according to FHO. Regression analyses were performed to study the relationship between anthropometric, lifestyle and sociodemographic variables, and each dietary pattern. Results Two dietary patterns were identified in both men and women : the Western pattern characterized by a higher consumption of red meats, poultry, processed meats, refined grains as well as desserts, and the Prudent pattern characterized by greater intakes of vegetables, fruits, non-hydrogenated fat, and fish and seafood. Similar Western and Prudent factor scores were observed in individual with and without FHO. In men with FHO+, the Western pattern is negatively associated with age and positively associated with physical activity, smoking, and personal income. In women with FHO-, the Prudent pattern is negatively associated with BMI and smoking and these pattern is positively associated with age and physical activity. Conclusion Two dietary patterns have been identified among men and women with and without FHO. Although that FHO does not seem to influence the adherence to dietary patterns, results of this study suggest that anthropometric, lifestyle and sociodemographic variables associated with dietary patterns differ according to FHO and gender.